2021
DOI: 10.1108/jsbed-09-2021-0360
|View full text |Cite
|
Sign up to set email alerts
|

Let the games begin: the relationship between video gaming and entrepreneurial mindsets

Abstract: PurposeThis article addresses the need for further conceptual development of the factors that influence the development of the entrepreneurial mindset. It focuses on finding a link between the classic mental models of entrepreneurship and those that are employed during video game play to explore if similarities exist.Design/methodology/approachUsing theories of entrepreneurship and opportunity recognition, the study examines a sample of 217 video gamers.FindingsThe results of this study suggest that an individ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
5

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 94 publications
0
5
0
5
Order By: Relevance
“…As pesquisas adicionam variáveis de um ou mais tipos de objetivos educacionais. Em síntese, independentemente do tipo de estudo, a literatura aponta que a utilização de gamificação na EE tem apresentado resultados positivos no aspecto cognitivo como: assimilação de conceitos, avaliação de riscos do negócio e tomada de decisões (Chemborisova et al, 2019); pensamento analítico (Pratikto et al, 2021); aprendizagem dos conteúdos por meio de desafios e resoluções de questões ou problemas reais (Capelo et al, 2021;Eggers et al, 2017;Fox et al, 2018;Kauppinen & Choudhary, 2021;Kraus et al, 2021).…”
Section: áRea De Formaçãounclassified
See 1 more Smart Citation
“…As pesquisas adicionam variáveis de um ou mais tipos de objetivos educacionais. Em síntese, independentemente do tipo de estudo, a literatura aponta que a utilização de gamificação na EE tem apresentado resultados positivos no aspecto cognitivo como: assimilação de conceitos, avaliação de riscos do negócio e tomada de decisões (Chemborisova et al, 2019); pensamento analítico (Pratikto et al, 2021); aprendizagem dos conteúdos por meio de desafios e resoluções de questões ou problemas reais (Capelo et al, 2021;Eggers et al, 2017;Fox et al, 2018;Kauppinen & Choudhary, 2021;Kraus et al, 2021).…”
Section: áRea De Formaçãounclassified
“…O potencial da gamificação é reforçado por Kraus et al (2021), que identificaram uma ligação entre os modelos mentais clássicos de empreendedorismo e aqueles que são empregados durante o jogo de videogame. Esses autores destacam que diferentes gêneros de jogos podem favorecer as cognições empreendedoras e, sobretudo, jogadores de games mais intensos -com tiros, por exemploapresentam maior desempenho, identificam oportunidades e são mais propensos ao empreendedorismo.…”
Section: Zichella E Reichstein (2022)unclassified
“…The studies add variables from one or more types of educational objectives. In summary, regardless of the type of study, the literature points out that the use of gamification in EE has shown positive results in cognitive aspects such as: assimilation of concepts, assessment of business risks and decision-making (Chemborisova et al, 2019); analytical thinking (Pratikto et al, 2021); learning content through challenges and solving real issues or problems (Capelo et al, 2021;Eggers et al, 2017;Fox et al, 2018;Kauppinen & Choudhary, 2021;Kraus et al, 2021).…”
Section: Appliedmentioning
confidence: 99%
“…Simulations can be combined with debriefing sessions or other strategies for participants to synthesize, present and reflect on the teachinglearning process (Capelo et al, 2021). The potential of gamification is reinforced by Kraus et al (2021), who identified a link between the classic mental models of entrepreneurship and those employed during video game play. These authors point out that different game genres can favor entrepreneurial cognitions and, above all, players of more intense games -with shots, for example -have higher performance, identify opportunities and are more prone to entrepreneurship.…”
Section: Zichella E Reichstein (2022)mentioning
confidence: 99%
“…Overall, topics such as risk and decision-making have often been neglected in studies that explore gamification in entrepreneurship teaching (Chapkovski et al, 2021;Zichella & Reichstein, 2022). In contrast, there is some evidence that gamification can affect risk aversion in undergraduate students (Kraus et al, 2021;Zichella & Reichstein, 2022). According to Kraus et al (2021), who used a sample of university students in the United States, the intensity and theme of the game have a moderating effect on risk propensity, so when the intensity of the game is high and involves many risky decisions, the subject's risk-taking orientation increases.…”
Section: Gamification and Risk Aversionmentioning
confidence: 99%